Evaluation of Kidney Pathologies – Pathogenetic and Functional Changes Caused By SARS-Cov-2 - Nurmuminovna, Gapparova Guli (American Journal of Botany and Bioengineering, 2024)
The coronavirus is highly infectious and highly tropism for kidney tissue. The new coronavirus infection can cause a wide range of pathological abnormalities in the kidneys. Various clinical forms of kidney damage in COVID-19 are caused by many pathogenetic mechanisms, such as direct cytopathic effect of the virus on kidney structures, endothelial dysfunction, cytokine storm, hemodynamic and water exchange disorders, renin-angiotensin-aldosterone damage. SARS-CoV-2 interacts with ACE2 receptors located on the endothelium of blood vessels and has a negative effect on the microvascular shell. Kidney damage in patients with COVID-19 includes nosological forms such as collapsing nephropathy, glomerulopathy, nephritis, acute tubular necrosis, exacerbation of autoimmune glomerulonephritis. During clinical observations, scientists from different countries found a connection between confirmed COVID-19 and the following laboratory data: hematuria, proteinuria, high levels of nitrogen in the blood, increased creatinine, uric acid, etc. were observed. In addition, the presence of risk factors in the patient, such as chronic kidney disease, cardiovascular pathology, immunodeficiency, taking nephrotoxic drugs, diabetes, hypertension, obesity, atherosclerosis, old age complicates the course of the disease and worsens the outcome. Thus, the pathological effect of the coronavirus on the body as a whole and on the kidneys in particular, the high mortality rate of patients with kidney pathology determines the urgency of studying this problem and finding ways to solve it.